Cooperative vehicular visible light communication in smarter split intersections - Vieira, Manuel Augusto (2022)
This paper addresses the issues related to the Visible Light Communication (VLC) usage in vehicular communication applications. We propose a Visible Light Communication system based on Vehicle-to-Vehicle, Vehicle-to-Infrastructure and Infrastructure-to-Vehicle communications able to safely manage vehicles crossing through an intersection leveraging Edge of Things facilities. By using the streetlamps, street lights and traffic signaling to broadcast information, the connected vehicles interact with one another and with the infrastructure. By using joint transmission, mobile optical receivers collect data at high frame rates, calculate their location for positioning and, concomitantly, read the transmitted data from each transmitter. In parallel with this, an intersection manager coordinates traffic flow and interacts with the vehicles via Driver Agents embedded in them. A communication scenario is stablished and a “mesh/cellular” hybrid network configuration proposed. Data is encoded, modulated and converted into light signals emitted by the transmitters. As receivers and decoders, optical sensors with light filtering properties, are used. Bidirectional communication between the infrastructure and the vehicles is tested. To command the passage of vehicles crossing the intersection safely queue/request/response mechanisms and temporal/space relative pose concepts are used. Results show that the short range mesh network ensures a secure communication from street lamp controllers to the edge computer through the neighbor traffic light controller with active cellular connection and enables peer-to-peer communication, to exchange information between V-VLC ready connected cars. The innovative treatments for the congested intersections are related with the introduction of the split intersection. In the split intersection a congested two-way-two-way traffic light controlled intersection was transformed into two lighter intersections which facilitate a smoother flow with less driver delay by reducing the number of vehicle signal phases. Based on the results, the V-VLC system provides direct monitoring of critical points including queue formation and dissipation, relative speed thresholds and inter-vehicle spacing, increasing safety.